Functioning of healthcare entities as learning organisations in Poland on the example of Podlaskie voivodeship - Czerska, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article aims to present issues regarding learning organisations in the context of the functioning of healthcare entities as examples of such organisations in Poland. A literature review was conducted, and the research problem and two research questions were formulated for verification. The subject of the study is public healthcare entities functioning as learning organisations in Poland, using the example of the Podlaskie voivodeship. In order to gather literature for the article, the desk research method was used, using scientific databases: Google Scholar and ScienceDirect. The literature on the subject covers the years 2015–2023. Firstly, the literature was reviewed, defining a learning organisation. Next, methods and tools used in organisational learning were listed. Lastly, the validity of medical entities as learning organisations was discussed. The next part of the article presented therapeutic entities from Podlaskie voivodeship as learning organisations in 2016–2022. The general criteria of the “Learning Organization” Competition were presented, followed by a discussion on the awarded therapeutic entities. In the end, the limitations of the article were discussed, and conclusions and practical implications were formulated. It was emphasised that changing and responding to market trends is essential for modern health organisations to sustain themselves in a turbulent market. The ability to constantly improve knowledge and search for it is crucial here. Therefore, in healthcare entities such as learning organisations, constant access to knowledge, not strictly medical, is crucial for medical and administrative staff. Helpful in the pursuit of this knowledge accumulation are various methods and tools that support the organisational learning and experience process.
Keywords: healthcare entity; learning organization; Podlaskie voivodeship; hospital